Synthesis of ZnO nanostructures using sol-gel method - J.N, Nor Hasnidawani; Hassan, Noor Azlina; Hassan, Norita; Bonnia, Noor Najmi; Ratim, Suzana; E. S., Ali (Elsevier B.V., 2016)
Zinc oxide plays an important role in current industry due to its special characteristics such as anti-corrosion, anti-bacteria, has low electrons conductivity and excellent heat resistance. Therefore, the objective of this study is to synthesize zinc oxide nanostructures with the most practical ways by using sol-gel method and characterize the nanostructures. Sol-gel method is the simplest method and has the ability to control the particle size and morphology through systematic monitoring of reaction parameters. ZnO nanoparticles were synthesized via sol gel method using Zinc acetate dehydrate (Zn(CH3COO)2.2H2O) as a precursor and ethanol (CH2COOH) was used as solvent, Sodium hydroxide (NaOH) and distilled water were used as medium. ZnO nanoparticles were characterized by using XRD, EDX, FESEM, and nano-particles analyser. Result of EDX characterization shows that the ZnO nanoparticles has good purity with (Zinc content of- 55.38% and; Oxygen content of- 44.62%). XRD result spectrum displays mainly oxygen and zinc peaks, which indicate the crystallinity in nature as exhibited. FESEM micrographs shows that synthesized ZnO have a rod-like structure. The obtained ZnO nanoparticles are homogenous and consistent in size which corresponds to the XRD result that exhibit good crystallinity. ZnO nanoparticles were successfully synthesized by sol-gel method in nanosize range within 81.28 nm to 84.98 nm.